(untitled) (Al-Mufassir: Jurnal Ilmu Alquran, Tafsir dan Studi Islam, 2022)
This article examines the educational function of the leadership of the Prophet, so it is urgent to become a leadership model. The author uses the inductive method. The result of the research is that the leadership actions of the Prophet Muhammad have values that show the aspects of education in directing his people towards the benefit of the world and the hereafter, both in matters of war leadership and leadership in worship.